Refined Calculation of Temperature Field in Cross-passage by Artificial Ground Freezing. Issue 1 (July 2021) - Lu, Xiangzhong; Zhang, Qingwu; Sun, Wenbin; Yan, Su; Zhang, Jiarong
Abstract: In China, the artificial ground freezing (AGF) method is widely used in the construction of cross-passages, however, it is difficult to accurately calculate the numerical solution of the freezing temperature field. In this paper, the boundary conditions in the numerical calculation are refined through in-suit measurements, and finally the freezing process of the connecting channel is effectively simulated. The calculation results show that the thickness and temperature of the frozen wall at 1.0 m near the main tunnel segment are significantly weakened. The frozen wall at the top of the cross-passage is affected by densely arranged holes, which is prone to excessive freezing. And based on the calculation results, an optimization plan for the highest cooling efficiency in the initial stage of active freezing and speeding up freezing is proposed.